INJAUAN YURIDIS TERHADAP WANPRESTASI PADA ASURANSI DI PT. ASURANSI TAKAFUL KELUARGA (STUDI PERKARA NO. 107/Pdt.G/2013/PN.Mdn) - Redha Rahayu; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Human life, consciously or not definitely at risk. Risk can come from a variety of things that are not expected, but from a possibility. It's just, how much risk would be faced by the person concerned, is very dependent on the activities undertaken. To cope with possible risks that can threaten at any time, where the risk can cause losses. Thus the role of non-bank financial institution insurance is needed. Insurance is divided into two konvensioanal insurance and Takaful. Insurance field problems are found, not only in conventional-based insurance namaun also in syariah-based insurance. As is the case between Bank Bukopin and Family Takaful Insurance Case Number 107/PDT.G/ 013/ PN.Mdn of default.The purpose of this paper is: first, to know the basic consideration of the judge in deciding case Number 107/PDT.G/2013/PN.Mdn. second, to determine the judge's decision No. 10/ PDT.G/ 2013/ PN.Mdn already meets the principles of legal certainty in determining the rights and obligations of the parties to the insurance agreement.This type of research can be classified into types of normative juridical research, because this research done through the written data by examining the literature data, the data source used, primary data and data tertiary secondary data, data collection techniques in this research with the literature method.From the research there are fundamental problems that can not pay the takaful insurance disimpulkan.pihak kopensasi fund insurance claims by Bank Bukopin. And also the evidence submitted was not examined because the court only ruled that the plaintiffs did not have legal standing to another investigation was not carried out. Because of the rights of the claimant or insurance clients are not met.Keywords: Overview - Default – PT. Insurance Takaful